The Dorobantu case and the applicability of the ECHR in the EU legal order - Mohay, Ágoston (Pécs journal of international and European law, 2020)
The applicability of the European Convention on Human Rights in the EU legal order has been a subject of scientific analysis and doctrinal debate ever since the relevance of fundamental rights in the EU legal order was made explicit by the Court of Justice of the European Union (CJEU). The EU not (or at least not yet) being a party to the Convention, the effects of the ECHR in EU law are indirect in nature, serving as a source of inspiration for the general principles of EU law and undoubtedly overlapping with the EU Charter of Fundamental Rights in numerous instances. In a recent judgment relating to the European Arrest Warrant, the CJEU however seemed to introduce a new way of application for ECHR law, one which in the author’s view goes beyond the Court’s hitherto applied method.